О ФАКТОРАХ ЭФФЕКТИВНОЙ РЕАЛИЗАЦИИ ИНВЕСТИЦИОННЫХ ПРОЕКТОВ - Мирхамидова Д. Н.; Атаханова Ш. С.; Соатов Ф. Й. (World Science, 2019)
In article researches on establishment of influence of geological and technology factors on efficiency of investment projects, determination of risks at implementation of investment projects in the oil and gas industry and feature and factors for successful implementation of investment projects are considered.